Commercial Security’s’ Effect on Security of Kenyans in Private Venues - Gerald Peter Mutonyi; Ann Sirera (Emerging Science Journal, 2018)
The strategic interplay between the Commercial security industry and security is complex. The realists view the provision of security as a fundamental obligation of the state. But to the liberalists, the pursuance of security can be achieved with the involvement of other actors offering the same. The question of whether the growing recognition of commercial security industry has marked an important shift in the norm of the state monopoly on violence in Africa needs answers. Despite this development, few studies have evaluated the effect of commercial security on security in Private Venues. Using Situational crime prevention theory, this study sort to demonstrate the effect of commercial security on security of Kenyans in Private Venues. The study adopted a cross sectional survey design, and was carried out in Nairobi with the target population of the adult residents in Nairobi. Customers and management of the commercial security industry were purposively sampled, whereas the general public and the security guards were systematically sampled. Questionnaire, interviews and structured observation were used to collect data.  Qualitative data was analysed thematically. While quantitative data was analysed using descriptive statistics like percentages, average and mean, and pie charts. There is an accepted positive effect on security of Kenyans in private functions and venues where commercial security present. But efficiency would be achieved if, the commercial security personnel provide indiscriminate security responses where there is a breach. Grey area needing legal backing were identified as: arming of the commercial security personnel, proper uniforms and kitting, and training and skills. It is expected that the findings of this study will be of great significance to the commercial security industry stakeholders in their quest to provide security to their customers. The findings will also be used to inform policy and practice that can beneficial to national security in Kenya. It is also hoped to stimulate the academic community and the government of Kenya towards more research in the field, and for the formulation of policies that will improve the general security of the citizens.